E-106 Efficacy of asahi fubuki as a guiding catheter for mechanical thrombectomy: an institutional case series. (4th August 2020) - Rinaldo, L; Cloft, H; Brinjikji, W
Abstract : Background: Delivery of a guiding catheter to a suitable position is a critical step in performing mechanical thrombectomy (MT) for treatment of acute stroke secondary to large vessel occlusion. Over the past several years, we have employed the Asahi Fubuki (Asahi Intecc Co., LTD, 1976) as a first-line guide catheter for the performance of MT. Herein, we reviewed the treatment outcomes of MT cases in which the Fubuki was utilized to assess the efficacy of this catheter. Methods: Radiology reports of MT for the treatment of acute stroke secondary to large vessel occlusion during which the Fubuki was employed as a guide catheter were retrospectively reviewed. Information on patient characteristics and treatment outcomes was collected. Predictors of failure to deliver the Fubuki to the cervical internal carotid artery (ICA) were identified using logistic regression analysis. Results: There were 124 patients who met the inclusion criteria for analysis. Mean patient age was 77.8 years and a slight majority of patients were female (50.8%). Large vessel occlusion occurred most often at the M1 segment (41.1%) and most occlusions occurred on the patient's right side (57.5%). The Fubuki was successfully delivered to the cervical ICA in 121 cases (97.6%), and the lesion was successfully crossed with the Fubuki as the guide catheter in 119 cases (96.0%). Herniation of the Fubuki into the aortic arch after delivery to the cervical ICA and cross-over to another guide catheter each occurred once (0.8%) in separate cases. Greater than or equal to TICI 2B revascularization was achieved in 100 patients (80.6%). Median times to lesion crossed and revascularization were 9 and 19 minutes. Conclusion: Our results indicate that the Asahi Fubuki is an effective guide catheter for the performance of MT. Disclosures: L. Rinaldo: None. H. Cloft: None. W. Brinjikji: None.